Novel benzoylurea derivative decreases TRPM7 channel function and inhibits cancer cells migration - Xiaoding Zhang; Rui Zong; Yu Han; Xiaoming Li; Shuangyu Liu; Yixue Cao; Nan Jiang; Pingping Chen; Haixia Gao (Taylor & Francis Group, 2024)
The transient receptor potential melastatin 7 channel (TRPM7) is a nonselective cation channel highly expressed in some human cancer tissues. TRPM7 is involved in the proliferation, migration, invasion, and epithelial-mesenchymal transition (EMT) of cancer cells. Modulation of TRPM7 could be a promising therapeutic strategy for treating cancer; however, efficient and selective pharmacological TRPM7 modulators are lacking. In this study we investigated N- [4- (4, 6-dimethyl- 2-pyrimidinyloxy) − 3- methylphenyl] -N' - [2 -(dimethylamino)] benzoylurea (SUD), a newly synthesized benzoylurea derivative, for its effects on cancer cell migration and EMT and on functional expression of TRPM7. Our previous studies showed that SUD induces cell cycle arrest and apoptosis of MCF-7 and BGC-823 cells (human breast cancer and gastric cancer cell lines, respectively). Here, we show that SUD significantly decreased the migration of both types of cancer cells. Moreover, SUD decreased vimentin expression and increased E-cadherin expression in both cell types, indicating that EMT is also decreased by SUD. Importantly, SUD potentially reduced the TRPM7-like current in a concentration-dependent manner and decreased TRPM7 expression through the PI3K/Akt signaling pathway. Finally, molecular docking simulations were used to investigate potential SUD binding sites on TRPM7. In summary, our research demonstrated that SUD is an effective TRPM7 inhibitor and a potential agent to suppress the metastasis of breast and gastric cancer by inhibiting TRPM7 expression and function.